The activity of creatine kinase in plasma of the elite men judo players during direct starting preparation - Blach, W. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
It has been well established that a single bout of severe exercise affects the activities of enzymes of muscle origin in blod or plasma. Changes in plasma activity of creatine kinase an enzyme located mainly in skeletal muscles and hear have attracted particular attention since the enzyme has been recognised as a marker of muscle damage in response to muscular work.Rational usage of training load requires searching for optimal methods of directing of the training process, based on the results of various types and forms of control. In many sports disciplines, as well in judo, there is the possibility of evaluating the competitors body reactions on the applied training load, on the basis of the enzyme CK (creatinine kinase) activity measurements in plasma. In elite sportsmen, whose training regimen require day to day strenuous activity during weeks before competition, a cumulation of metabolic disturbances may occur affecting their performance. The aim of the study was to evaluate the effect of exercise during training sessions on the changes in creatine kinase activity in the blood plasma of judo contestans, during direct competition preparation to European Championships.